2002
DOI: 10.1016/s0735-1097(01)01718-1
|View full text |Cite
|
Sign up to set email alerts
|

Onset heart rate of microvolt-level T-wave alternans provides clinical and prognostic value in nonischemic dilated cardiomyopathy

Abstract: The OHR of TWA is of additional prognostic value in DCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 36 publications
3
68
1
Order By: Relevance
“…7 Nonsustained VT and frequent ventricular ectopy increase in prevalence with heart failure severity and have predicted sudden and non-sudden death. 3,11,12 ICDs did not improve survival compared with no antiarrhythmic therapy or with amiodarone in patients with nonischemic cardiomyopathy selected for nonsustained VT (S. Adam Strickberger, MD, Washington Hospital Center, Washington, DC, oral and electronic communication, 2001) or depressed ventricular function. 13 Invasive electrophysiological studies detect potential reentry circuits after myocardial infarction.…”
Section: See P 565mentioning
confidence: 99%
See 3 more Smart Citations
“…7 Nonsustained VT and frequent ventricular ectopy increase in prevalence with heart failure severity and have predicted sudden and non-sudden death. 3,11,12 ICDs did not improve survival compared with no antiarrhythmic therapy or with amiodarone in patients with nonischemic cardiomyopathy selected for nonsustained VT (S. Adam Strickberger, MD, Washington Hospital Center, Washington, DC, oral and electronic communication, 2001) or depressed ventricular function. 13 Invasive electrophysiological studies detect potential reentry circuits after myocardial infarction.…”
Section: See P 565mentioning
confidence: 99%
“…17 Detection of small oscillations in the T-wave amplitude (T-wave alternans) during exercise is linked to susceptibility to ventricular arrhythmias. 12 It is associated with high-risk groups and was a marker of risk in a prospective study of 85 patients with nonischemic cardiomyopathy. 12 Trials to determine if T-wave alternans testing can be used to select patients for ICD therapy are in progress.…”
Section: See P 565mentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies conducted in patients without implanted ICDs have found MTWA to be a highly accurate risk stratifier and, in particular, have found that the rate of ventricular tachyarrhythmic events (VTEs) among patients who test MTWA negative is exceedingly low [1][2][3][4][5][6][7] suggesting that ICD therapy may not benefit such patients 8 . As a result, MTWA has been proposed as a means of guiding implantable cardioverter defibrillator (ICD) therapy in patients with risk factors for SCD but without a prior history of sustained VTEs (primary prevention patients).…”
Section: Introductionmentioning
confidence: 99%